Financial analysis : the next step - Gill, James O. (Crisp Pub. Menlo ParkUS, 1992)
Reviews basics of financial statements and includes sample documents and practice problems. Examines the elements of corporate financial statements including balance sheet and cash flow statement. Discusses asset management and the three decision shaping tools of financial planning. Explains how to read annual reports.